Pengaruh Penggunaan Internet dan Dukunga Orang Tua terhadap Prestasi Belajar Siswa Kelas VII MTs Ma’arif Bakung Udanawu Kabupaten Blitar - Eli Fatmawati; Jani Jani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The internet is needed and used by students as a learning resource to obtain, add to and assist in completing school assignments, and students also need parental support such as school supplies, vehicles, learning facilities, school uniforms, education costs and pocket money. When these two factors are implemented well, good student learning achievement will also be created. The formulation of the problem in this thesis is (1) Is there an influence of internet use on the learning achievement of class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency, academic year 2023/2024? (2) Is there an influence of parental support on the learning achievement of class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency in the 2023/2024 academic year? Meanwhile, the objectives of this research are (1) To understand the influence of internet use on the learning achievement of class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency, academic year 2023/2024. (2) To understand the influence of parental support on the learning achievement of class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency, academic year 2023/2024. This research uses quantitative research, with a type of causal research. The objects of this research are all class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency for the 2023/2024 academic year with a population of 300 students and a sample of 30 students. The technique used in collecting data was by distributing questionnaires to class VII students. Data analysis techniques use research instrument tests, classical assumption tests and multiple linear regression tests. The results of the research show, 1) Partially there is a positive and significant influence between internet use on learning achievement as indicated by the results of t-count > t-table (3.561 > 2.051). 2) Partially there is a positive and significant influence between parental support on learning achievement as shown by the results of t-count > t-table (3.925 > 2.051).